Tiletamine/zolazepam and dexmedetomidine with tramadol provide effective general anesthesia in rats. Issue 1 (2nd January 2021) - Limprasutr, Vudhiporn; Sharp, Patrick; Jampachaisri, Katechan; Pacharinsak, Cholawat; Durongphongtorn, Sumit
Abstract: Background: Tiletamine/zolazepam is a dissociative anesthetic combination commonly used in small animals but information is limited in rats. The alpha‐2 agonist, dexmedetomidine, has gained popularity in laboratory animal anesthesia. Tramadol is a weak opioid mu agonist. The aim of this study was to assess whether the tiletamine/zolazepam/dexmedetomidine (ZD) combination effectively provides a surgical anesthesia plane comparable to tiletamine/zolazepam/dexmedetomidine with tramadol (ZDT) in a minor procedure in rats. Methods: Rats were induced with ZD or ZDT. After the loss of paw withdrawal, a small incision was made on the rats' left thighs as a surgical stimulus. Rats were maintained under a surgical anesthesia plane by assessing the loss of the paw withdrawal reflex for 45 minutes, then atipamezole was administered. Monitored anesthesia parameters included: (a) physiological parameters – pulse rate (PR), respiratory rate (RR), tissue oxygen saturation (%SpO2 ), and body temperature; (b) duration parameters – induction time, onset and duration of surgical anesthesia plane, onset of recovery, and recovery time. Results: PR was significantly lower at 10 minutes in ZD and 5 minutes in ZDT groups. No difference was observed for RR, %SpO2, and body temperature. Likewise, there were no differences for duration parameters: induction time was less than 3 minutes; onset and duration of surgical anesthesia plane were approximately 5 and 45 minutes, respectively; onset of recovery (time to move) was 51 minutes; and recovery time was 52 minutes, respectively. Conclusion: These data suggest the ZD combination provides a surgical anesthesia plane comparable to ZDT in a rat incisional pain model.